2016
DOI: 10.1021/acs.iecr.6b00242
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel Tubular Ceramic Membrane for Water and Heat Recovery from Waste Gas Streams

Abstract: For the first time, we report a multichannel ceramic tubular membrane for water and heat recovery from gas streams. Mass and heat transfer performances of the multichannel tubular membrane are systematically investigated and compared with those of a monochannel tubular membrane. Compared with the monochannel tubular membrane, the multichannel membrane has much larger mass and heat transfer resistances, leading to lower mass and heat transfer rates. Operational parameters (e.g., fluid velocities and transmembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 28 publications
1
30
1
Order By: Relevance
“…Interestingly, it appears that this trend is against the boundary layer heat and mass transfer theory, and is totally different from previous results using water vapor saturated gas stream as the feed [19,23,27]. Mass and heat transfer rates should increase or be relatively stable with the rise in fluid flow rate when the boundary layer effect is significant or insignificant, respectively [32][33][34][35].…”
Section: Effect Of Gas Flow Ratecontrasting
confidence: 66%
See 3 more Smart Citations
“…Interestingly, it appears that this trend is against the boundary layer heat and mass transfer theory, and is totally different from previous results using water vapor saturated gas stream as the feed [19,23,27]. Mass and heat transfer rates should increase or be relatively stable with the rise in fluid flow rate when the boundary layer effect is significant or insignificant, respectively [32][33][34][35].…”
Section: Effect Of Gas Flow Ratecontrasting
confidence: 66%
“…Compared with the recovery performance from saturated gas streams, water and heat recoveries from unsaturated flue gas with the same type of membranes are much lower [19].…”
Section: Effect Of Gas Flow Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Instead of carrying out a study using conventional flue gas, Gao et al [24] carried out a study to research the effect of SO 2 on ceramic membrane extracting water. A multi-channel ceramic membrane in place of a single membrane was used for experimental studies by Yue et al [25]. It was revealed that the multi-channel membrane tube had a lower mass transfer rate and heat recovery rate by comparing the two types of tubes.…”
mentioning
confidence: 99%